AAU-BOT1: A Platform for Studying Dynamic, Life-Like Walking. Issue 3 (18th June 2009) - Svendsen, Mads Sølver; Helbo, Jan; Hansen, Michael Rygaard; Popovic, Dejan B.; Stoustrup, Jakob; Pedersen, Mikkel Melters
Abstract : This paper describes the development of the humanoid robot AAU-BOT1. The purpose of the robot is to investigate human-like walking and in this connection, test prosthetic limbs. AAU-BOT1 has been designed with modularity in mind making it possible to replace, e.g. the lower leg to test transfemoral or transtibial prosthesis or orthosis. Recorded motion data from a male test person, along with approximated inertial and mass properties, were used to determine necessary joint torques in human walking which was used as design parameters for the robot. The robot has 19 degrees of freedom (DoF), 17 actuated and 2 unactuated acting as passive toe joints. The project was granted 60, 000 Euro, and to keep development costs below this, the development and instrumentation was carried out by three groups of master students from the Department of Mechanical Engineering (ME) and the Department of Electronic Systems at Aalborg University and supported by the Department of Health Sciences and Technology (HST). To further reduce the cost, the robot uses off-the-shelf hardware which also reduced the time from idea to practical implementation. The result is a low-cost humanoid robot fully assembled and equipped with sensors ready to take its first steps.